2015
DOI: 10.1371/journal.pone.0119555
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Effect of Hypoxia on Tumor Progression and Liver Progenitor Cell Markers in Primary Liver Tumors

Abstract: Background & AimsExpression of liver progenitor cell (LPC) characteristics has been proposed as a negative prognostic marker in primary liver tumors. Hypoxia has been linked to activation of the Notch pathway which is responsible for activation and proliferation of LPCs and hypoxia-induced LPC activation has been shown in hepatocellular carcinoma. Our aim was to elucidate the time-dependent effects of hypoxia on the LPC niche in hepatocellular carcinoma which could aid in determining a safe time frame for use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 40 publications
(58 reference statements)
1
20
1
Order By: Relevance
“…S3). Although low glucose level could also induce a high level of GLUT-1, hypoxia would be the most possible cause of the increased GLUT-1 in our study due to the following reasons: GLUT-2, instead of GLUT-1, mediates glucose uptake in hepatocyte (14); therefore, a low glucose level in liver cancer cells may not trigger the overexpression of GLUT1; there is a documented strong association between hypoxia and liver tumor (15,16) that correlated the increased hypoxia with the observation of high level of the GLUT-1 in our study.…”
Section: Resultsmentioning
confidence: 75%
“…S3). Although low glucose level could also induce a high level of GLUT-1, hypoxia would be the most possible cause of the increased GLUT-1 in our study due to the following reasons: GLUT-2, instead of GLUT-1, mediates glucose uptake in hepatocyte (14); therefore, a low glucose level in liver cancer cells may not trigger the overexpression of GLUT1; there is a documented strong association between hypoxia and liver tumor (15,16) that correlated the increased hypoxia with the observation of high level of the GLUT-1 in our study.…”
Section: Resultsmentioning
confidence: 75%
“…The first pathway is cHC‐CC that arises as a conventional HCC at the early stage, and acquires biliary and/or SC features during its progression . Ischaemia and previous treatments have been suggested to contribute to the acquisition of biliary features and the enrichment of ‘cancer SCs’ in liver carcinoma . As TERT mutations are frequently detected in HCC but not in CC, TERT mutations may indicate the histogenesis of cHC‐CC via HCC corresponding to INT.…”
Section: Discussionmentioning
confidence: 99%
“…8 Ischaemia and previous treatments have been suggested to contribute to the acquisition of biliary features and the enrichment of 'cancer SCs' in liver carcinoma. 29 As TERT mutations are frequently detected in HCC but not in CC, 9,10,16 TERT mutations may indicate the histogenesis of cHC-CC via HCC corresponding to INT. Another pathway is cHC-CC arising as a biphenotypic carcinoma at the early stage.…”
Section: Discussionmentioning
confidence: 99%
“…If the increased serum LDH levels reflect whole liver hypoxia, as described above, and such circumstances decrease the effect of sorafenib, we hypothesize that a pretreatment hypoxic situation could increase tumor aggressiveness or promote drug resistance. Recently, using mouse models of primary liver tumors, Bogaerts et al showed that hypoxia in advanced stages resulted in increased expression of liver progenitor cell characteristics that indicate a poor outcome (23). Liu et al demonstrated that the targeted knock-down of hypoxia-inducible factor-2α, which is associated with cell proliferation under hypoxic conditions, in combination with sorafenib, markedly decreased proliferation in HCC cells (24).…”
Section: Discussionmentioning
confidence: 99%